Decline in ICU adverse events, nosocomial infections and cost through a quality improvement initiative focusing on teamwork and culture change. Issue 4 (2nd August 2006) - Jain, M; Miller, L; Belt, D; King, D; Berwick, D M
Abstract : Background: Nosocomial infections occur in approximately 10% of patients in intensive care units (ICUs). Several studies have shown that a quality improvement initiative can reduce nosocomial infections, mortality, and cost. Context: Our hospital is located in Northern Mississippi and has a 28 bed Medical-Surgical ICU unit with 95% occupancy. We joined the ICU collaborative with the IMPACT initiative of the Institute of Healthcare Improvement (IHI) in October 2002. A preliminary prospective before (fiscal year (FY) 2001–2) and after (FY 2003) hypothesis generating study was conducted of outcomes resulting from small tests of change in the management of ICU patients. Key measures for improvement: Nosocomial infection rates, adverse events per ICU day, average length of stay, and average cost per ICU episode. Strategy for change: Four changes were implemented: (1) physician led multidisciplinary rounds; (2) daily "flow" meeting to assess bed availability; (3) "bundles" (sets of evidence based best practices); and (4) culture changes with a focus on the team decision making process. Effects of change: Between baseline and re-measurement periods, nosocomial infection rates declined for ventilator associated pneumonia (from 7.5 to 3.2 per 1000 ventilator days, p = 0.04) and bloodstream infections (from 5.9 to 3.1 per 1000 line days, p = 0.03), with a downward trend in the rate of urinary tract infections (from 3.8 to 2.4 per 1000 catheter days, p = 0.17). There was a strong downward trend in the rates of adverse events in the ICU as well as the average length of stay per episode. From FY 2002 to FY 2003 the cost per ICU episode fell from 3406 to 2973. Lessons learned: A systematic approach through collaboration with IHI's IMPACT initiative may have contributed to significant improvements in care in the ICU setting. Multidisciplinary teams appeared to improve communication, and bundles provided consistency of evidence based practices. The flow meetings allowed for rapid prioritization of activity and a new decision making culture empowered team members. The impact of these changes needs to be assessed more widely using rigorous study designs.